Soil variability and crop yield gaps in two village landscapes of Burkina Faso - Diarisso, Tidiane; Corbeels, Marc; Andrieu, Nadine; Djamen, Patrice; Douzet, Jean-Marie; Tittonell, Pablo Adrian (Springer, 2019)
Low crop yields in the savannah zones of West Africa are commonly attributed to rainfall deficits and poor soil fertility. In this study, an assessment was made on how the position of fields belonging to different farm types can explain soil variability and related crop yield gaps in two villages in Burkina Faso, Yilou and Koumbia, located, respectively, in the Sudano-Sahelian and Sudanian agroecological zones. In each village, four farm types were identified. Soil fertility was generally poor and use of nutrient inputs low in most of the farmer’s fields . As a consequence, yields for most crops were low, but differences among farm types were found, which can be linked to their socioeconomic characteristics that influence the amount of inputs used. Application of fertilizers differed also between fields within farms and tended to be greater on the fields near the homesteads in the village of Yilou, especially for organic fertilizers. At both villages, the rates of N and K inputs were insufficient to compensate for their respective output rates, leading to negative partial nutrient balances . The existence of patchworks of soil fertility gives rise to a wide variation in crop responses to fertilizers. Exploitable yield gaps were substantial and to a large extent related to the low fertility status of soils and suboptimal fertilizer applications.